Architectural competitions in interwar (1918-1940) Lithuania: general tendencies / Konkursai tarpukario (1918–1940) Lietuvoje: bendrosios tendencijos - Vaidas Petrulis (Journal of Architecture and Urbanism, 2013)
The article discusses relevant, but so far little examined topic – architectural competitions interwar Lithuania (1918–1940). It is obvious that the culture of competitions was very noticeable and significant part of architectural processes. The majority of important public buildings, and even a significant part of less important projects was built with reference to competitions. The architectural competition as a means to achieve the best result was strongly supported by public policy, as well as by various public societies and private business. The main objective of this article, which is based on archival materials and studies of media of the time, is to reveal the characteristics of organization of competitions, to give a qualitative analysis of the phenomenon. The paper discuss various types of competitions, analyzes requirements, public transparence, the level of internationality, activities of competition commissions, the impact of social and professional environment of competition results. The text also discusses the implementation of competitive works, reveals the level of criticism which follows the process of architectural competition. Finally, the review is being completed with observations about political expectations of clients and the level of implementation of these aspirations.